Penerapan Metode Expressing Writing Therapy Dalam Mereduksi Stress Kerja Pada Karyawan Rumah Makan Kalimasada Mencimai - Ghofur, Muh. Abdul; Andriani, Andriani (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Work-related stress commonly arises due to the heavy workload, causing employees to feel pressure in their jobs. Additionally, the demands of targets and the accumulation of tasks are some of the smaller factors that trigger stress among workers. Expressive Writing Therapy (EWT) is an approach that involves writing freely and honestly about one’s feelings, experiences, and thoughts, especially those related to emotional or traumatic experiences. The main goal of this therapy is to help individuals express and process repressed emotions that are often difficult to articulate through direct verbal communication. In this study, the researcher used a qualitative descriptive method. A qualitative descriptive research method is an approach used to deeply and thoroughly describe phenomena, events, or issues that occur in the field. At Kalimasada Restaurant, in implementing the Expressive Writing Therapy method, employees are asked to write their expressions in four sections: the first part is to write about what is troubling their thoughts; the second part is a gratitude journal; the third part is hopes and prayers; and the last part is suggestions, critiques, and ideas for the improvement of Kalimasada Restaurant. Employee responses to this method were very positive. They stated that this method not only serves as a means to reduce stress but also as a form of leadership’s attention to employees, which helps create a family-like and comfortable work environment